Impacts of Heronries on Water Quality as Evaluated through Escherichia coli and Fecal Sterol Analyses. (1st June 2017) - Telesford‐Checkley, Judlyn M.; Mora, Miguel A.; Gentry, Terry J.; McDonald, Thomas J.; Boellstorff, Diane E.
ABSTRACT: : The authors used fecal sterol analysis to determine the potential contribution of E. coli from heronries to waterbodies in east‐central Texas. They analyzed E. coli and fecal sterol concentrations in samples from four heronries during the breeding seasons in 2011–2013. The highest E. coli concentrations were in water samples from the two largest heronries established directly over water. The main sterols in fecal samples were cholesterol and stigmasterol, and in water, cholesterol, coprostanol, and cholestanol. Total sterols ranged 979 to 5838 ng/g dry weight in fecal samples, and 13 to 600 ng/L in water samples. There was a positive correlation between E. coli and the sum of bird sterols in water exposed directly to fecal deposition, but not in water surrounding the heronries. The authors found a strong association between E. coli and stigmasterol, suggesting that the presence of stigmasterol in water could be used for predicting E. coli sources from heronries nesting close to waterbodies.